Kajian Kualitas Nutrisi Pakan Terhadap Produktivitas Ayam Kampung Super di Kabupaten Lombok Timur - Purnamasari, Dwi Kusuma; Erwan, Erwan; Syamsuhaidi, Syamsuhaidi; Sumiati, Sumiati; Wiryawan, K.G.; Maslami, Vebera; Salsabila, G. (LPPM Universitas Mataram, 2024)
The aim of the study was to determine the type and nutritional quality of feed and its effect on the productivity of super kampung chickens in The East Lombok Regency. This research was conducted by collecting data from ten farmers with a minimum population of a thousand super kampung chickens in East Lombok. Parameters observed were the type of feed used, the nutritional content of the feed, feed consumption, harvest weight, and feed conversion. The data obtained are tabulated and then discussed descriptively by comparing the nutritional content, feed consumption, harvest weight, and feed conversion obtained with the Indonesian Nasional Standard (SNI). Based on the results of the research conducted all breeders who were the target of the study used complete feed. There are 6 types of complete feed that are used and come from 4 different companies, namely GM-PS, GM-1EJ, SB11, HDBR1-168LCR, 811K NEWHOPE, HDBR 161 A. The feed consumption obtained ranges from 1.5-3.15 kg with an average of 2.26 kg/head/period. Harvested weight ranged from 0.84-0.91 kg/head with an average of 0.87 kg/head with an FCR value of 2.68. The conclusion of this study is that in general the nutritional content and quality of the feed used have met the standards based on SNI, but not followed by productivity that meets the standards.